Analisis Maqāṣid al-Sharī’ah Yusuf Qardhawi dan Abdullah Ibn Baz Tentang Hukum ‘Azl - Trisnantaasari, Yullyta Eka (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2021)
This study aims to describe Yusuf Qardawi and Abdul Aziz bin Abdullah bin Baz idea about the law of 'azl and find out the opinion of Yusuf Qardawi and Abdul Aziz bin Abdullah bin Baz about the law of 'azl in terms of Maqāṣ̱id shari'ah perspective. The purpose of marriage is that one of them wants to carry out a lineage, but some couples still want to focus on careers, work and managing economic problems, therefore they want to postpone pregnancy first, as for the way they are taken to prevent pregnancy, namely by doing 'azl. 'Azl is an effective way of not using other contraceptives. This study reviews about 'azl (interrupted intercourse) in the perspective of Maqāṣid shari'ah. The method that the author uses in this research is a qualitative method. In this study there are three data, namely primary, secondary, tertiary. The data collection method used by the author is a literature study in the form of data from various literary sources. The data analysis technique used by the author is descriptive data analysis. To explain analyzing the existing data, the author compares maqāṣid shari'ah against the views of Yusuf Qardawi with Abdul Aziz bin Abdullah bin Baz on the law of 'azl. The findings from this study are that Yusuf Qardhawi's opinion if 'azl is associated with Maqāṣid shari'ah then it is classified as a ḥājīyāt need. It because a married couple can manage pregnancy and the number of children they want, while the opinion of Abdul aziz bin Abdullah bin baz if 'azl is associated with Maqāṣid Shari'ah is classified as a dharūrīyat need because he wants Muslims to become many.